Enhancing a Tangible Tabletop with Embedded-Technology Objects for Experiencing Deep Time - Mendoza, Yusseli Lizeth Méndez; Baranauskas, M. Cecília (Anais do Workshop de Informática na Escola (WIE); 2019: Anais do XXV Workshop de Informática na Escola, 2019)
Abstract concepts are harder to understand because they do not provide a direct sensory reference as concrete concepts do. Tangible interfaces have been shown benefits to facilitate the learning of such concepts through the manipulation of physical objects. In this work, we investigate the use of TangiTime, an educational exhibit designed and constructed as a tangible tabletop enhanced with embedded-technology objects to explore the concept of deep time. In particular, we were interested in the role of embedded-technology objects to support engagement and learning. We describe the TangiTime design process and artifacts implementation. Also, we present the context in which the exhibit was put into usage and results. Our results indicate that interaction with embedded-technology objects creates new ways of experiencing tangible tabletops and more engagement with the theme of the exhibit.